Pelatihan Perawatan Solar Cell Untuk Menjaga Unjuk Kerja Pembangkit Listrik Tenga Surya (PLTS) - Muh. Nurkoyim Kustanto; Nasrul Ilminnafik; Muhammad Dimyati Nashrullah; Haidzar Nurdiansyah (Journal of Community Development, 2024)
The increasing demand for energy and the depletion of oil reserves are forcing humans to seek alternative energy sources. Therefore, the need for alternative electrical energy sources arises, namely, by utilizing solar panels. The importance of understanding how solar panels work and their maintenance becomes a determining factor in ensuring the optimal performance of Solar Photovoltaic (PV) Systems. Lack of knowledge and awareness about maintenance can result in decreased efficiency and lifespan of solar panels. Users of Solar Photovoltaic (PV) Systems are also expected to understand its maintenance procedures. Thus, the implementation of this community service activity aims to educate the public and enable them to maintain Solar Cells as Solar Photovoltaic (PV) Systems. This activity is carried out by providing direct training on PV system maintenance, both theoretically and practically. The impact of this community service activity is that the community can understand and maintain Solar Cells as Solar Photovoltaic (PV) Systems, as evidenced by the evaluation results where the understanding of the training participants falls into the category of very knowledgeable, which is 80.88%.